441 Influence Of Chronotype On CPAP Adherence. (3rd May 2021) - Adekolu, Olurotimi; Xu, Zhichao; Chu, Jen-hwa; Kushida, Clete; Yaggi, Henry; Knauert, Melissa; Zinchuk, Andrey
Abstract: Introduction: Continuous positive airway pressure therapy (CPAP) is an efficacious treatment for obstructive sleep apnea (OSA). However, despite interventions targeting established determinants of CPAP use, adherence to CPAP remains poor. An Individual's chronotype can influence behavior including adherence to dietary changes and alcohol abstinence. We hypothesized that chronotype will be associated with CPAP adherence and aimed to identify the mechanisms of this association. Methods: Secondary data analysis of the active CPAP arm (n=469) from the Apnea Positive Pressure Long-term Efficacy Study, a multicenter randomized controlled trial of CPAP therapy in a sleep clinic population was performed. The Morningness-Eveningness Questionnaire (MEQ) was used to identify three chronotype categories: Evening (MEQ score: 16–41), Neither (42–58) and Morning (59–86) types. CPAP adherence over 6-months (hours/night) was objectively measured using smart-card downloads. Linear mixed modelling evaluated the association between the chronotype and CPAP adherence, adjusting for confounders (e.g., age). Mechanisms of this association were examined by change in beta estimates for the chronotype with addition of a potential mediator (e.g., sleep duration). Results: There were 206(44%), 38(8%) and 219(47%) Morning, Evening and Neither chronotype patients respectively. Evening types were youngest (48.0±13.4 vs. 50.3±11.3 and 56.3±11.4 years, p<0.001) with highest body mass index (BMI, 34.9±10.5 vs. 31.2±10.5 and 32.7±10.5 kg/m2, p=0.006) and longest sleep on weekends (7.9±2.0 vs. 7.3±1.3 and 7.6±1.5 hours, p=0.017) compared to Morning and Neither types. A higher proportion of Evening types also reported symptoms of insomnia and fatigue (p-values 0.017 and 0.048 respectively). CPAP adherence, however, did not differ between Evening and Neither types (p=0.276). Compared to the Neither types, Morning types exhibited significantly higher CPAP adherence (β= 40mins/night, p=0.001) with a slight decrease after adjusting for age, sex, race, marital status, education, and OSA severity (β= 33mins/night, p=0.012). Sleep duration, insomnia, BMI and fatigue mediated a minimal proportion of this effect (0.7–3.7%). Conclusion: In this cohort of sleep clinic patients, the Morning chronotype was associated with better CPAP adherence. Only a small proportion of this association was mediated by observed clinical differences between the chronotypes. Understanding the influence of chronotype on CPAP use may provide novel insight for improving OSA therapy effectiveness. Support (if any):